2002
DOI: 10.1074/jbc.m109793200
|View full text |Cite
|
Sign up to set email alerts
|

Role of CBP/p300 and SRC-1 in Transcriptional Regulation of the Pulmonary Surfactant Protein-A (SP-A) Gene by Thyroid Transcription Factor-1 (TTF-1)

Abstract: Surfactant protein-A (SP-A

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
77
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(83 citation statements)
references
References 61 publications
(80 reference statements)
6
77
0
Order By: Relevance
“…Intrafamilial phenotypic variation in this disorder may be explained by differences in modifier genes that produce a different genetic background in the same family. Indeed, the activity of TITF-1 is highly dependent on its interactions with other transcription factors and coactivators, including GATA-6, NF-1, RAR, CBP/p300, SRC-1, and TAZ [29][30][31][32][33][34]. In addition, deficient transcriptional activity of mutant TITF-1 (p.P202L) was completely rescued by cotransfection of wild-type PAX8 in HEK293 cells [13].…”
Section: Discussionmentioning
confidence: 94%
“…Intrafamilial phenotypic variation in this disorder may be explained by differences in modifier genes that produce a different genetic background in the same family. Indeed, the activity of TITF-1 is highly dependent on its interactions with other transcription factors and coactivators, including GATA-6, NF-1, RAR, CBP/p300, SRC-1, and TAZ [29][30][31][32][33][34]. In addition, deficient transcriptional activity of mutant TITF-1 (p.P202L) was completely rescued by cotransfection of wild-type PAX8 in HEK293 cells [13].…”
Section: Discussionmentioning
confidence: 94%
“…For example, TTF-1 interacts with GATA6 to activate SP-C and Wnt7b transcription (47,67). Transcriptional co-activator TAZ and NFI interact with TTF-1 and synergistically activate the SP-C gene (65,68), whereas surfactant protein A and SP-B transcription is regulated by interaction of TTF-1 with CREB-binding protein and SRC-1 (66,69). TTF-1 also interacts with RAR/RXR and BR22 (66,70) to activate SP-B transcription.…”
Section: Discussionmentioning
confidence: 99%
“…SRC-3, also known as AIB1 (amplified in breast cancer), was reported originally in breast cancer in which gene amplification was occurred frequently and the expressions of SRC-3 were observed in several human tumors including breast cancer [2,5,6,9]. Temporal and spatial expressions of SRC-3 are coincident with CCSP expression pattern in the Clara cells of the lung [12] and in which CCSP could play an important role in the early lung development [22].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, TTF-1 could serve as a major regulator of CCSP gene expression [17,24], and it has been reported that TTF-1 could interact with the SRC [22]. Thus, TTF-1 might play important role in the lung development and lung tumor progression in combination with SRC-3.…”
Section: Introductionmentioning
confidence: 99%